A Case Study and Clinical Implications of Antenatal Allergic Reaction to Parenteral Iron During Pregnancy - Chandru , S Shanmuga; Immanuvel, T; Adhiraj , B; Karthickeyan, K.; Sundaram, . P. Shanmuga; Dheenadhayalan, M; Sri, M.K. Sundar (Journal of Neonatal Surgery, 2025)
Iron deficiency anemia (IDA) is the most widespread food deficiency prostration in the world, particularly, associated with deficiency among girls of procreative age. IDA is another important source of morbidity and fatalities connected with pregnancy, especially in underdeveloped countries such as India. In patients with poorly tolerated oral iron, intravenous iron formulations, including iron sucrose, is an effective treatment of moderate-to-severe anemia. Nevertheless, sometimes they might also lead to development of hypersensitivity reactions, resulting in the need of immediate medical assistance. In this case, a 26-year-old female patient (G2P1L1) who was admitted for an elective repeat cesarean procedure at 38 weeks of gestation is described. Her vitals were stable, and she had palpitations. In preoperative tests, mild microcytic anemia, leukocytosis, hypokalemia, and elevated CRP and serum IgE values were detected, which may indicate a possible allergic propensity. On the first postoperative day after intravenous iron sucrose, she developed a type I hypersensitivity reaction that was facilitated by urticaria, flushing, itching, dyspnea, and hypotension. Using hydrocortisone and IV pheniramine maleate (Inj. Avil), the response was well controlled. Oral iron supplementation was started and parenteral iron was stopped. The present case emphasizes how crucial it is to monitor the allergic reactions when receiving parenteral iron therapy, particularly in individuals who have high inflammatory signs.